Kaizen Peningkatan Lama Belajar di Luar Jam Sekolah Siswa Olimpiade Matematika di Sekolah Islam Athirah Makassar melalui Penerapan Pengingat Belajar - Rahmi, Nur Rahmi; Markianto, Oky; Fildzah Zahra, Muthia (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2025)
This pre-experimental study aimed to increase the duration of students' mathematics learning outside of school hours using a learning reminder application. The research employed a One-Shot Case Study Design and was conducted at Athirah Islamic School. The sample consisted of four junior high school students and three senior high school students who were part of the Mathematics TOSA program. Due to differences in academic load, the target learning intensity for junior high school TOSA students was set at 10 hours per week, while for senior high school students, it was 6 hours per week. Descriptive statistical analysis was used to evaluate the data. The results indicated that after one month of receiving learning reminders in the first cycle, the average mathematics learning intensity outside of school hours increased by 2.3 hours per week for junior high school students and 2.53 hours per week for senior high school students. In this first cycle, 50% of the junior high school students reached the target of 10 hours per week, whereas none of the senior high school students achieved the target of 6 hours per week. However, after three weeks in the second cycle, the average learning intensity increased to 12.76 hours per week for junior high school students and 7.56 hours per week for senior high school students, with 100% of the students meeting their respective targets. In conclusion, the use of a learning reminder application effectively increased the mathematics learning intensity among both junior and senior high school students outside of school hours, demonstrating its potential as a tool to enhance student learning outcomes.